Clinical implications of DNMT3A mutations in a Southeast Asian cohort of acute myeloid leukaemia patients. Issue 8 (18th January 2017) - Tan, Marcus; Ng, Isaac K S; Chen, Zhaojin; Ban, Kenneth; Ng, Christopher; Chiu, Lily; Seah, Elaine; Lin, Mingxuan; Tai, Bee Choo; Yan, Benedict; Ng, Chin Hin; Chng, Wee-Joo
Abstract : Aims: In recent years, genomic technologies have enabled the identification of mutations in acute myeloid leukaemia (AML). DNMT3A is a recurrently mutated epigenetic modifier gene in AML. To date, the prognostic significance of DNMT3A mutations has not been studied in a Southeast Asian AML population. We sought to investigate the clinical implications of DNMT3A mutations in a Southeast Asian cohort of AML patients. Methods: DNMT3A mutations were identified using a targeted next-generation sequencing panel in 157 AML patients. We studied the molecular and clinical features of patients with DNMT3A mutations and assessed the prognostic impact of DNMT3A mutations. Results: DNMT3A mutations were found in 33 of 157 (21.0%) AML patients. 114 patients were included for statistical analysis. Pretreatment data revealed that patients with DNMT3A mutations were older (≥60 years old), had a higher white blood cell count at diagnosis, had more adverse cytogenetic risk profiles and were more often associated with NPM1 mutations compared with patients with wild-type DNMT3A . Survival analysis showed that DNMT3A mutations were associated with poorer clinical outcomes. This was especially when associated with NPM1 and FLT3-ITD mutations (AML NPM1/FLT3/DNMT3A ), which are common. The AML NPM1/FLT3/DNMT3A subtype was an independent predictor for poorer overall survival (OS). Other independent risk factors for poorer OS include advanced age at diagnosis and adverse cytogenetic risk stratification. Conclusions: DNMT3A mutations are associated with an unfavourable clinical outcome in our Southeast Asian AML patient cohort. In particular, AML NPM1/FLT3/DNMT3A patients had the poorest prognosis.